Meningkatkan Perilaku Prososial Anak Dengan Teknik Islamic Storytelling Finger Doll - Indah Fajrotuz Zahro (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2018)
Development of technology era replaces existence human orientation. Children tend to be individualized and difficult to adapt theirself in their environment. Beside that, the condition of emotion are difficult to control. In this condition, the children tend not to be able to attention and consider to the obtaining norms. Some less behaviors adaptif often arise when the children are in negatif emotion, for instance aggressive. Emotion and social development are important aspects to be noticed in childhood. The ability of children to recognize theirself depend on theirs ability for adapting and engaging their social environment. The children with low social skills tend to have unsatisfactory relationships and receiving negative feedback from the social environment. One of the things that can be done to develop children's emotional social skills is to practice social behavior. This article aims to explain the relevance of islamic storytelling finger doll techniques to increase the children's prosocial behavior. The implementation stage of islamic story telling finger doll is to identify the characters, determine the setting of the story, interpret the story and the value contained, reflection and observation. Based on the Qur'an and hadith, human beings are perfected by sighting, hearing and heart to be grateful as human beings. The role of educators are to stimulate the mind and mentality of children to be able to know the feelings of self and others, so that it becomes an altruistic generation and make a good relationships with the others.